Nanomat Li–S batteries based on all-fibrous cathode/separator assemblies and reinforced Li metal anodes: towards ultrahigh energy density and flexibility. Issue 1 (24th August 2018) - Kim, Jung-Hwan; Lee, Yong-Hyeok; Cho, Sung-Ju; Gwon, Jae-Gyoung; Cho, Hye-Jung; Jang, Minchul; Lee, Sun-Young; Lee, Sang-Young
Abstract : Nanomat Li–S batteries based on all-fibrous cathode/separator assemblies and reinforced Li metal anodes are presented to enable ultrahigh-energy-density and flexibility. Abstract : Lithium–sulfur (Li–S) batteries have attracted considerable attention as a promising alternative to current state-of-the-art lithium-ion batteries (LIBs), however, their practical use remains elusive, which becomes more serious upon application to flexible/wearable electronics. Here, we demonstrate a new class of nanomat Li–S batteries based on all-fibrous cathode–separator assemblies and conductive nonwoven-reinforced Li metal anodes as an unprecedented strategy toward ultrahigh energy density and mechanical flexibility. Sulfur cathodes, which are fibrous mixtures of sulfur-deposited multi-walled carbon nanotubes and single-walled carbon nanotubes, are monolithically integrated with bi-layered (pristine cellulose nanofiber (CNF)–anionic CNF) paper separators, resulting in metallic foil current collector-free, all-fibrous cathode–separator assemblies. The cathode–separator assemblies, driven by their all-fibrous structure (contributing to three-dimensional bi-continuous electron/ion conduction pathways) and anionic CNFs (suppressing the shuttle effect via electrostatic repulsion), improve redox kinetics, cyclability and flexibility. Nickel-/copper-plated conductive poly(ethylene terephthalate) nonwovens are physically embedded into Li foils to fabricate reinforced Li metal anodes with dimensional/electrochemical superiority. Driven by the structural uniqueness and chemical functionalities, the nanomat Li–S cells provide exceptional improvements in electrochemical performance (the (cell-based) gravimetric/volumetric energy density = 457 W h kgcell −1 /565 W h Lcell −1 and the cycling performance (over 500 cycles) under 110% capacity excess of the Li metal anode) and mechanical deformability (they even can be crumpled).